Quantitative High-Energy π p Scattering Predictions from Low-Energy Phase Shifts - Ferro Fontan, C.; Odorico, R.; Masperi, L. (1968)
Fil: Ferro Fontan, C. Facultad de Ciencias Exactas y Naturales, Universidad de Buenos Aires; Argentina